PENGALAMAN BILINGUAL MAHASISWA KELAS INTERNASIONAL PROGRAM STUDI HUBUNGAN INTERNASIONAL UNIVERSITAS ISLAM NEGERI SUNAN AMPEL (UINSA) SURABAYA - Atiq M. Romdlon; Abu Fanani; Murni Fidiyanti; zudan rosyidi; Imam Hanafi; Rachmat Efendi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Bilingual experience is the experience of language users when they actively use two languages ​​in their daily activities. The construction of this experience is shaped by the environment and context that encourage and require to use English as a second language (L2). The subjects in this study were 24 students from the class of 2022 in the International Relations Study Program at Sunan Ampel State Islamic University (UINSA) Surabaya. This research used a mixed methods approach with an explanatory design that utilized qualitative methods to deepen the analysis of data obtained through quantitative methods. To measure bilingual experience, a questionnaire was used containing four indicators: the use of English as a second language (L2) on campus, the use of English as a second language (L2) in social and family settings, media and learning resources to improve English proficiency, and strategies for using English as a second language (L2). These indicators also served as a reference in developing the interview guide. The data were analyzed using descriptive statistics techniques with the help of SPSS 21 software, further enhanced by interview results. The results of the correlation test narrowed down to two groups. The first group is the bilingual experience variable group with